Identifying the mediating role of corporate reputation in the relationship between selected RepTrak facets and customer loyalty of Malaysia Airlines Berhad - Chan, Tak Jie; Su, Lin Tay; Huam, Hon Tat; Adzharuddin, Nor Azura (Taylor's University, 2020)
Corporate reputation is a part of the intangible asset management that can help create a competitive advantage in firms. Hence, it is crucial for firms to create a favourable reputation and build a good perception among stakeholders. However, crises are inevitable and can cause a firm’s reputation to be tarnished and its credibility to be questioned. Therefore, this study aims to identify the mediating role of corporate reputation on the relationship between selected facets of the RepTrakTM reputation model, namely, products/services, innovation, citizenship, leadership, performance and customer loyalty from the perspective of Malaysia Airlines Berhad’s (MAB) customers. Online and offline questionnaires were administered to MAB consumers which yielded 173 valid responses. The collected data were then analysed using partial least square structural equation modelling (PLS-SEM) in Smart-PLS 3.2.7. The findings confirmed the positive relationships between the four facets of RepTrakTM with corporate reputation in the current context; however, innovation demonstrated a negative but significant relationship with corporate reputation. In addition to that, the relationship between corporate reputation and customer loyalty was also established. Further, the results confirmed corporate reputation as a mediator that mediates the relationship between all five determinants of RepTrakTM model and customer loyalty. The conclusion, the implications and suggestions for future research are also discussed.